Soft Hydrogels with Double Porosity Modified with RGDS for Tissue Engineering - Podhorská, Bohumila; Chylíková-Krumbholcová, Eva; Dvořáková, Jana; Šlouf, Miroslav; Kobera, Libor; Pop-Georgievski, Ognen; Frejková, Markéta; Proks, Vladimír; Janoušková, Olga; Filipová, Marcela; Chytil, Petr (Macromolecular bioscience, 2024)
This study develops and characterizes novel biodegradable soft hydrogels with dual porosity based on N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers cross-linked by hydrolytically degradable linkers. The structure and properties of the hydrogels are designed as scaffolds for tissue engineering and they are tested in vitro with model mesenchymal stem cells (rMSCs). Detailed morphological characterization confirms dual porosity suitable for cell growth and nutrient transport. The dual porosity of hydrogels slightly improves rMSCs proliferation compared to the hydrogel with uniform pores. In addition, the laminin coating supports the adhesion of rMSCs to the hydrogel surface. However, hydrogels modified by heptapeptide RGDSGGY significantly stimulate cell adhesion and growth. Moreover, the RGDS-modified hydrogels also affect the topology of proliferating rMSCs, ranging from single-cell to multicellular clusters. The 3D reconstruction of the hydrogels with cells obtained by laser scanning confocal microscopy (LSCM) confirms cell penetration into the inner structure of the hydrogel and its corresponding microstructure. The prepared biodegradable oligopeptide-modified hydrogels with dual porosity are suitable candidates for further in vivo evaluation in soft tissue regeneration.
Keywords: poréznost; Tissue Engineering; mesenchymal stem cells; Hydrogels; double porosity hydrogels; N-(2-hydroxypropyl)methacrylamide; scaffolds for tissue engineering; Porosity; buněčná adheze; Tissue Scaffolds; tkáňové podpůrné struktury; Cell Adhesion; hydrogels; tkáňové inženýrství; mezenchymální kmenové buňky; Mesenchymal Stem Cells; hydrogely